NUMERALIA BAHASA JAWA KUNO - Carma Miradayanti, Dewa Ayu (Humanis; Volume 4. No. 3. September 2013, 2013)
The numerable research of ancient Javanese is based on the unique things which appear in this numeral of ancient javanese. Which as the fact that there is numeral which derives from Sanskrit and it is also used in Ancient Javanese. Beside that, the numerable research of Ancient Javanese has not done yet before. The purpose of this research is to describe the forms and the characteristics of the numeral of Ancient Javanese. This research was analyzed based on the structural theory by Ferdinand de Saussure. The dichotomy that is used in this research is synchronic analysis, signifiant-signifie, langue-parole and syntagmatic-paradigmatic relationship. Formly, this numeral of Ancient Javanese can be divided into two. They are, base numeral and derivational numeral. The derivational numeral can also be divided into three, they are, the numeral of affix, duplication and combination. The characteristics that differenciate the numeral of Ancient Javanese and the other word classes are morphology and syntax.
Keywords: numeral, form, characteristic. 1. Latar